1997
DOI: 10.1093/qjmed/90.6.417
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B and C in doctors and dentists in Nigeria

Abstract: We surveyed a random sample (n = 75) of doctors and dentists at University College Hospital, Ibadan, Nigeria. They were offered anonymous testing for hepatitis B surface antigen (HBsAg), hepatitis Be antigen (HBeAG), antibodies to hepatitis B core antigen (anti-HBc) and to hepatitis C virus (anti-HCV), by enzyme immunoassay. The results suggest a high prevalence of hepatitis B virus (HBV) with a high potential of transmissibility, as well as a high prevalence of HCV infection. The majority of the doctors and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
5
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 1 publication
2
43
5
2
Order By: Relevance
“…The previous observation of greater reporting of vaccination among older dentists 11,12 with a longer length of time working in this profession 3,12 was not found in this study. This finding shows that older cohorts were being replaced by others that had already had access to information about infection control measures, so that such variables could no longer distinguish groups in terms of reported vaccination.…”
Section: Discussioncontrasting
confidence: 95%
See 3 more Smart Citations
“…The previous observation of greater reporting of vaccination among older dentists 11,12 with a longer length of time working in this profession 3,12 was not found in this study. This finding shows that older cohorts were being replaced by others that had already had access to information about infection control measures, so that such variables could no longer distinguish groups in terms of reported vaccination.…”
Section: Discussioncontrasting
confidence: 95%
“…This association was not previously observed 3,11,12,20,22 , although these variables may refer to care for one's own health. Thus, dentists who do not consume tobacco or alcoholic beverages may be more concerned about their health, like workers who have been vaccinated.…”
Section: Discussioncontrasting
confidence: 42%
See 2 more Smart Citations
“…8 Among doctors and dentists in Ibadan, Nigeria, a high prevalence of HBV was reported with a high potential for transmissibility. 9 A study in Brazil showed that seropositivity for HBV infection was high among dentists. 10 Another study among dentists in Khartoum, Sudan showed that only 52% of the dentists had undertaken HBV vaccination.…”
Section: The Present Scenariomentioning
confidence: 99%